Hrvatsko-slovenski paralelni korpus - Požgaj-Hadži, Vesna (Array, 2000)
The Slovene-Croatian Parallel Corpus is a project that was launched together with about twenty others within the framework of bilateral academic and research co-operation between Slovenia and Croatia. The corpus will contain one million words (500, 000 for each language) and will comprise texts of various functional styles – both Croatian originals and their Slovene translations and vice versa. We are choosing texts that were created after 1990 in order to represent the languages to be contrasted in their present state. The need for the compilation of this type of corpus was initiated by various fields simultaneously: the teaching of both languages at university level, translation studies, lexicographic research, contrastive studies, and also by the translators of these languages themselves. Particularly the latter as well as other language professionals will be able to use the parallel corpus as an additional source of information, even more valuable in view of the fact that at present we do not have a proper Croatian-Slovene (Slovene-Croatian) dictionary. This contribution is trying to show preliminary statistical results of text alignment illustrated on the test sample which includes eight bilateral agreements between both states.